Adverse late health outcomes among children treated with 3D radiotherapy techniques: Study design of the Dutch pediatric 3D‐RT study. Issue 2 (30th January 2023) - Beijer, Josien G. M.; Kok, Judith L.; Janssens, Geert O.; Streefkerk, Nina; de Vries, Andrica C. H.; Slagter, Cleo; Maduro, John H.; Kroon, Petra S.; Grootenhuis, Martha A.; van Dulmen‐den Broeder, Eline; Loonen, Jacqueline J.; Wendling, Markus; et al.
Abstract: Background: Adverse late health outcomes after multimodal treatment for pediatric cancer are diverse and of prime interest. Currently available evidence and survivorship care guidelines are largely based on studies addressing side‐effects of two dimensional planned radiotherapy. Aims: The Dutch pediatric 3D‐planned radiotherapy (3D‐RT) study aims to gain insight in the long‐term health outcomes among children who had radiotherapy in the 3D era. Here, we describe the study design, data‐collection methods, and baseline cohort characteristics. Methods and Results: The 3D‐RT study represents an expansion of the Dutch Childhood Cancer Survivor study (DCCSS) LATER cohort, including pediatric cancer patients diagnosed during 2000–2012, who survived at least 5 years after initial diagnosis and 2 years post external beam radiotherapy. Individual cancer treatment parameters were obtained from medical files. A national infrastructure for uniform collection and archival of digital radiotherapy files (Computed Tomography [CT]‐scans, delineations, plan, and dose files) was established. Health outcome information, including subsequent tumors, originated from medical records at the LATER outpatient clinics, and national registry‐linkage. With a median follow‐up of 10.9 (interquartile range [IQR]: 7.9–14.3) years after childhood cancer diagnosis, 711 eligible survivors were identified. The most common cancer types were Hodgkin lymphoma, medulloblastoma, and nephroblastoma. Most survivors received radiotherapy directed to the head/cranium only, the craniospinal axis, or the abdominopelvic region. Conclusion: The 3D‐RT study will provide knowledge on the risk of adverse late health outcomes and radiation‐associated dose‐effect relationships. This information is valuable to guide follow‐up care of childhood cancer survivors and to refine future treatment protocols.